Reversibility of the Socialist Realism Aesthetics (on the Example of the Modern Russian Cinematography) / Реверсивность эстетики социалистического реализма (на примере современного российского кинематографа) - YEFANOV ALEXANDER A. / ЕФАНОВ А.А. (Наука телевидения)
The article studies reversibility of socialist realism aesthetics—a trend in the modern Russian cinematography—from a socio-cultural perspective. An integrative cultural-philosophical approach serves as research optics. It combines the features of the traditional cultural method (focusing on the basic units of culture—material products and works of art—and behavior patterns formed on their basis) and aesthetic approach (an appeal to the reflective study of expressive forms of art products and their influence on mass consciousness, as a result of which mass culture is constructed). The potential of an integrative cultural-philosophical approach is revealed through a set of methods: historical and genetic analysis, modeling, and case studies. The empirical base are films representing historical events in the blockbuster format, which have been released by Russian production companies for wide distribution between 2015 and 2021 (The Balkan Line, The Age of Pioneers, Going Vertical, Donbass: Outskirts, AK-47, Crimea, Legend No. 17, The Last Frontier, Salyut 7, Panfilov’s 28 Men). The conclusion is that socialist realism aesthetics, through the cultivation of a pro-Russian narrative, is designed to emphasize in the mass consciousness the distinctness of the Russian state from the point of view of its unique status, which largely determines the situation of confrontment on the global stage, thereby denoting the instrumental nature of cinema products, endowing the institution of cinema the role of an idealistic propagandist of our times. Статья посвящена социокультурному изучению существующей в современном российском кинематографе тенденции реверсивности эстетики социалистического реализма. В качестве исследовательской оптики выбирается интегративный культурфилософский подход, сочетающий в себе черты традиционного культурологического подхода (фокусирование на базисных единицах культуры — материальных продуктах, произведениях искусства и формирующихся на их основе образцах поведения) и эстетического подхода (апелляция к рефлексивному изучению выразительной формы продуктов искусства и ее влияния на массовое сознание, в результате чего конструируется массовая культура). Используется комплекс методов, раскрывающий потенциал интегративного культурфилософского подхода: историко-генетический анализ, моделирование, кейс-стади. Эмпирическую базу составляют кинопродукты, репрезентирующие исторические события, объединенные форматом блокбастера, выпущенные российскими производящими компаниями, выходившие в широкий кинопрокат («Балканский рубеж», «Время первых», «Движение вверх», «Донбасс. Окраина», «Калашников», «Крым», «Легенда № 17», «Подольские курсанты», «Салют-7», «28 панфиловцев»). Хронологические рамки исследования: 2015–2021 годы. По итогам проведенного исследования делается вывод, что эстетика социалистического реализма посредством культивирования пророссийского нарратива призвана подчеркивать в массовом сознании самобытность российского государства с точки зрения его уникального статуса, во многом детерминирующего ситуацию противостояния на международной арене, тем самым обозначая инструментальный характер продуктов кинематографа и наделяя институт кино ролью идеалистического пропагандиста современности.